Implementasi Maqashid Asyari’ah dalam Perlindungan Data Pribadi Penggunaan Media Sosial - Muhamad Bachrul Ulum; Lukman Nur Hakim; Raden Muhammad Hilmi Maulana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The emergence of social media promotes interaction and sharing of information, however, it also heightens the potential for breaches and the inappropriate use of personal information. This research intends to investigate how maqashid sharia can be applied to safeguard the personal data of social media users, serving as an ethical and religious underpinning in today’s digital landscape. From a theoretical perspective, this research situates the protection of personal data within the context of positive law and maqashid sharia principles, particularly hifz al-nafs, hifz al-‘aql, and hifz al-mal, which prioritize the protection of life, intellect, and property against digital threats. The research employs a qualitative methodology through literature-based analysis involving documentation, which is then evaluated descriptively and analytically in relation to pertinent literature, regulations, and academic articles. Findings indicate that the implementation of maqashid sharia is pertinent to enhancing awareness regarding digital privacy, fostering user vigilance when sharing personal information, and advocating for the accountability and openness of digital platforms. Therefore, maqashid sharia serves as an ethical foundation for ensuring that social media usage is safe, principled, and focused on benefiting society.